Vasopressin & Oxytocin in Control of the Cardiovascular System: An Updated Review - Japundžić-Žigon, Nina; Lozić, Maja; Šarenac, Olivera; Murphy, David (Current Neuropharmacology, 2020)
Since the discovery of vasopressin (VP) and oxytocin (OT) in 1953, considerable knowledge has been gathered about their roles in cardiovascular homeostasis. Unraveling VP vasoconstrictor properties and V1a receptors in blood vessels generated powerful hemostatic drugs and drugs effective in the treatment of certain forms of circulatory collapse (shock). Recognition of the key role of VP in water balance via renal V2 receptors gave birth to aquaretic drugs found to be useful in advanced stages of congestive heart failure. There are still unexplored actions of VP and OT on the cardiovascular system, both at the periphery and in the brain that may open new venues in treatment of cardiovascular diseases. After a brief overview on VP, OT and their peripheral action on the cardiovascular system, this review focuses on newly discovered hypothalamic mechanisms involved in neurogenic control of the circulation in stress and disease.
Keywords: hypertension